Parallel and Distributed Logic Programming Towards the Design of a Framework for the Next Generation Database Machines - Bhattacharya, Alakananda; Konar, Amit; Mandal, Ajit K. (Studies in Computational Intelligence, 2006)
The book Parallel and Distributed Logic Programming provides a clear introduction to parallel and distributed approach to logic programming. It examines the existing models of distributed logic programming, analyses the pros and cons of these models, and proposes an alternative framework for distributed logic programming using extended Petri nets. The hardwired realization of the Petri net based framework is presented in detail. Principles of mapping of a logic program on to the proposed framework are also outlined. Finally, the book attempts to explore the scope of Petri net models in designing deductive database machines of the next generation.